Regenerative facades for hotel retrofitting in hot-dry climate - Amina Batagarawa; Aminu Bn Musa (Multidisciplinary Adaptive Climate Insights)
Nigeria, despite its vast oil and gas resources, faces significant challenges in electricity generation, resulting in an average daily power supply of only 9 hours. This inadequate power supply poses a major obstacle to economic diversification in non-oil-producing states like Kebbi. The hospitality sector in Birnin Kebbi struggles with high operational costs due to reliance on diesel generators, contributing to environmental degradation and hindering investments. This study evaluates the regenerative energy potential of retrofitting hotel facades in Hot-Dry climate. Energy audits in target hotel and data collection on electricity bills, diesel consumption, and building characteristics reveal significant energy-saving opportunities. The data collected is used to simulate regenerative energy facade strategies for retrofitting hotels, including shading, glazing, thermal mass, and insulation. Base-case modelling shows that wall improvements and insulation materials like rock wool or glass wool can reduce energy consumption by over 30%. Using lighter-coloured wall surfaces with higher Solar Reflectance Index (SRI) can further enhance energy savings. Additionally, implementing windows with improved insulation properties and shading devices can reduce energy consumption. These findings underscore the importance of incorporating regenerative energy facade strategies in building designs and policies in Nigeria to promote sustainable development. Further research should focus on long-term performance evaluations and cost-benefit analyses of these strategies.   Received: 26 October 2024 Accepted: 19 December 2024 Published: 25 December 2024